Improving Critical Thinking Skills through Mathematics Textbooks Integrated with a Challenge-Based Learning Model in a STEM Context Assisted by Quizizz Application - Adi Satrio Ardiansyah; Eni Lestari; Karunia Ma’ariffatun (Universitas Syiah Kuala, 2025)
The challenge to develop critical thinking skills resonates both for education in general or mathematics education. Developing a mathematics textbook that integrated Challenge based on STEM Context Learning assisted by Quizizz is an option to answer this challenge. Development research with the 4D model has been carried out with a focus on developing a product that is feasible, easy to understand, effective in improving critical thinking skills, and has a good response from students. Data was collected using interview techniques, questionnaires and tests which were then analyzed qualitatively, descriptive quantitatively, and a number of parametric statistical tests. The results show that the mathematics textbook that integrated Challenge based on STEM Context Learning assisted by Quizizz is feasible as seen from the average score of 92.66%, easy to understand as seen from the average score of 98%, effective in improving critical thinking skills as seen from the achievement of the research hypothesis, and has a good response from students as seen from the average score of 94.6%. Further implementation as a form of dissemination and adoption needs to be carried out by teachers in the classroom so that the challenge of developing critical thinking skills can be carried out properly